Positive leadership in healthy organizational - Sánchez Montero, Ivanna (2021)
The objective of the research is to determine the implications of positive leadership within healthy organizations, with the intention of offering alternatives for obtaining satisfactory results and breaking with traditional work schemes. The research approach is qualitative of the documentary type, supported by the hermeneutical method, using the technique of triangulation of sources to interpret the collected data. The results reflect that positive leadership becomes a tool that integrates responsibility with the emotions of the workers, becoming a strategy for healthy organizations to emerge as innovators and a role model. Another result is the creation of a system (SARF) that serves as a guide for the recognition of the positive effects generated by the use of a program based on positive leadership. The conclusions suggest that positive leadership generates a beneficial paradigmatic change in healthy organizations, proving that the unification between managerial and emotional issues opens communicational spaces that, when properly focused, generate strategic scenarios to make correct decisions for the well-being of all those involved. In the organization.